The supernatant of Lactiplantibacillus plantarum 25 is more effective than extracellular vesicles in alleviating ulcerative colitis and improving intestinal barrier function - Gong, Shuang; Li, Xin; Zhang, Qiong; Wang, Rui; Zeng, Ruixia; Zhang, Yibo (Frontiers in Microbiology, 2026)
IntroductionLactiplantibacillus plantarum (L. plantarum) has been reported to attenuate ulcerative colitis (UC) and restore intestinal barrier integrity. However, it remains unclear whether culture supernatant or extracellular vesicles (EVs) are more effective.MethodsUC was induced in mice to compare the effects of L. plantarum 25 (LP25) supernatant and EVs on disease severity, survival, and tight junction protein expression. Gut microbiota and metabolism were analyzed by 16S rRNA sequencing and untargeted metabolomics. In vitro, LPS-stimulated Caco-2 cells and a Caco-2/RAW 264.7 co-culture model were used to evaluate barrier integrity, immune responses, and TLR4/NF-κB pathway activation.ResultsCompared with EVs, LP25 supernatant significantly improved survival, alleviated disease severity, preserved tight junction protein expression, modulated gut microbiota, enhanced intestinal functional protein expression, and inhibited macrophage TLR4/NF-κB activation.DiscussionLP25 supernatant exerts superior protective effects compared with EVs in alleviating UC and maintaining intestinal barrier function, highlighting its potential as a functional component for dietary interventions targeting inflammatory bowel diseases.